Indicators of the speed movement in juvenile in rowing on kayaks - Bogush, V.; Getmantsev, S.; Yatsunskiy, O.; Bogatyirev, K.; Verteleckiy, O.; Reznichenko, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to study the indicators of the physical quality of the speed and its constituent elements.